The Role of Endocrine Disruptors and Environmental Chemicals in Causing Cancer: Focusing on Genetic and Epigenetic Mechanisms - Singh, Amit Kumar; Choudhary, Ranjay Kumar; Tiwari, Vikas; Kondaveeti, Suresh Babu; Kaur, Jappreet; Garg, Vivek Kumar; Sharma, Bunty; Aggarwal, Vaishali; Buttar, Harpal (Scripta Medica, 2026)
To address the effects of exposure to endocrine-disrupting chemicals (EDCs), it is essential to conduct comprehensive literature researches and clarify the role of EDCs in cancer development and progression. These chemicals can influence key cellular pathways through various mechanisms, including histone modifications, DNA methylation, epigenetic changes, and abnormal microRNA (miRNA) expression. Nevertheless, it remains unknown whether the epigenetic changes caused by EDCs can help predict adverse results. Hence, understanding how the interplay of environmental, genetic, and epigenetic factors of different endocrine disruptors interacts with the modifications and regulation of signaling pathways is crucial. Several studies with EDCs, including cadmium, bisphenol A, arsenic, lead, phthalates, polychlorinated biphenyls, parabens, dioxins, and organochlorines, have been shown to have adverse effects on the epigenome. Additionally, numerous studies have explored the impact of EDCs on lifestyle factors. Understanding how endocrine-disrupting chemicals function at the genetic, epigenetic, and molecular levels, and considering the potential effects of EDC exposure, is crucial for enhancing knowledge about intergenerational cancer transmission.